The effect of humor on the level of anxiety of uterine cancer patients undergoing hysterectomy - Negradas, Robelita C.
Cancer is one of the fatal diseases without a sure cure. In the Philippines, it is now being considered as the 4th leading cause of mortality. Uterine cancer, a malignancy that affects many women has a delibitating effect on quality of life. The effect ranges from physical to psychosocial, and the most common manifestations are fear, worry and anxiety. The diagnosis and management phase of cancer bring about such manifestations. Bio-behavioral interventions have proven effective in alleviating these feelings. One pf these interventions is humor therapy. Humor and laughter can counteract these negative thoughts or feelings. The power of humor, which consists of its physical, social, psychological and emotional functions has provided relief among many. It physiological function promotes a pattern of relaxation on the person, increases arterial and venous circulation promoting better circulation of oxygen, nutrients, immune elements and phagocytes, and it helps the body participate in the process of analgesia.Humor, considered universal, has long been a part of the Filipino culture. This makes this unique form of bio-behavioral therapy very applicable in our society.The study was done mainly to determine the effect of humor on the anxity level of uterine cancer patients who were scheduled for hysterectomy. Specific questions were:1. What is the humor profile of uterine cancer patients who were scheduled for hysterectomy?2. What is the socio-demographic profile of uterine cancer patients who were scheduled for hysterectomy?3. What is the relationship of the intervening variables, namely socio-demographic profile, role functions, support system, and spirituality to the uterine cancer patient's level of anxity?4. Is there a significant difference in the level of anxiety of uterine cancer patients who were scheduled hysterectomy before and after exposure to humor?5. Is there a significant difference in the level of anxiety of uterine cancer patients between the study and the control group?Twenty uterine cancer patients who have undergone hysterectomy had consented to become subjects in this study. They were admitted to the Philippine General Hospital Ward 14-B (Malignancy Ward). Purposive sampling was used in the selection of subjects. The assignment of participants was done in such a way that the first five clients who came in for hysterectomy were assigned to the control group first, the next five to study group, until the twenty samples were evenly assigned to the two groups.An assessment of anxiety level, humor and socio-demographic profile was done using a Likert type rating scale: State Trait Anxiety Inventory (STAI, by Spielberger) for anxiety, and Humor Assessment Tool (made by the investigator) for Humor. Included as a tool was a questionnaire on socio-demographic data. All tools were translated to Filipino, and they were pilot tested before finally used. The Filipino comedy films used to elicit laughter were the following: (1) "Home Along Da Riles," (2) "Tropang Trumpo," (3) "Mixed Nutrs," (4) "Bubble Gang".The interrupted time series with no treatment control group time series, was the type of quasi-experimental design used due to uncontrollable situations or variables during the data gathering period.T-test for two independent samples and analysis of variance (ANOVA) were the statistical tests used in testing the two hypotheses, and these were set at 0.5 and 0.10 level of confidence. Other statistical treatments were also applied, i.e. frequencies, percentages or rates and the Pearson Product Moment Correlation to determine if the intervening variables were related to the anxiety level of participants.